2011
DOI: 10.1590/s1806-37132011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de Mycobacterium bovis em cepas micobacterianas isoladas espécimes clínicos humanos em um complexo hospitalar na cidade do Rio de Janeiro

Abstract: In 2005 and 2006, 8,121 clinical specimens submitted to the Mycobacteriology Laboratory of the Clementino Fraga Filho University Hospital/Thoracic Diseases Institute, in the city of Rio de Janeiro, Brazil, were inoculated on Löwenstein-Jensen medium containing glycerol and pyruvate. There were 79 mycobacteria isolates that presented growth only on pyruvate-containing medium, and those isolates were selected for the presumptive identification of Mycobacterium bovis. The selected isolates were screened with bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…Studies in Mexico have reported a greater prevalence, with annual rates of up to 40% [4]. In Brazil, published studies on this issue are rare, and some of them did not find M. bovis strains in samples of human tuberculosis [5,6]. In contrast, a study in the state of Minas Gerais showed that M. bovis accounted for 1.6% of the mycobacterial isolates obtained from patients with tuberculosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Mexico have reported a greater prevalence, with annual rates of up to 40% [4]. In Brazil, published studies on this issue are rare, and some of them did not find M. bovis strains in samples of human tuberculosis [5,6]. In contrast, a study in the state of Minas Gerais showed that M. bovis accounted for 1.6% of the mycobacterial isolates obtained from patients with tuberculosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…bovis nos casos humanos de tuberculose e isso se deve aos fatos de que a sintomatologia clinica, as lesões patológicas e o tratamento da doença causada pelo M. bovis e pelo Mycobacterium tuberculosis (M. tuberculosis) são similares (DE LA RUA-DOMENECH, 2006) e impedem uma caracterização específica do agente (THOEN et al, 2009;SOBRAL et al, 2011). Salienta-se que a metodologia diagnóstica mais comumente utilizada diminui a chance de crescimento do Mycobacterium bovis, se presente (SOBRAL et al, 2011), ou não diferencia os membros do complexo M. tuberculosis (ROCHA et al, 2012), dificultando, então, a obtenção de dados sobre prevalência de infecção por M. bovis em humanos.…”
Section: Lista De Quadrosunclassified
“…No Brasil a prevalência da doença causada por M. bovis em bovinos e bubalinos é considerada baixa (~ 1,3% dos rebanhos nacionais) e o controle é regulamentado pelo Programa Nacional de Controle e Erradicação da Brucelose e da Tuberculose Animal (PNCEBT) (BRASIL, 2006). Pouco se sabe sobre a real prevalência de M. bovis em humanos (DE KANTOR et al, 2008;SOBRAL et al, 2011;SILVA et al, 2013). Já em animais selvagens, os poucos relatos dessa doença são referentes à animais mantidos em cativeiro, e não se sabe se algum animal silvestre poderia atuar como reservatório e ter capacidade de potencializar a transmissão do patógeno entre rebanhos domésticos ou animais selvagens (ZIMPEL et al, 2017).…”
unclassified